A relação das crianças com jardim botânico: um espaço para ciência - Souza, Débora de (2015)
This dissertation entitled: "The relationship of children with the Botanical Garden: a place for Science" had as its central objective to analyze the relationship that children have with science through the experiences lived in the Adolpho Ducke Botanical Garden. For this, we use theoretical assumptions that subsidize the conception of science that we have adopted in the context of research. We also emphasize the relationship between children and science, making a dialogue with the sociology of childhood and their interactions with nonformal space. It is a qualitative research of accompanied visits selected 03 groups, totaling twenty-six (26) children of both sexes between six to eleven (6-11) years old, with the participation of three (03 ) monitors that have made monitoring during visits. The names of these groups were inspired by the Amazon fish names on display on site, as follows: Group 1: Tambaqui, Group 2 and Group 3 Pirarucu: Jaraqui. Because it is research with children, we seek theoretical contributions that enhance children's participation in the construction of our methodological approach, so we conducted participant observation, conversation wheel, field records and photographs. It was found that space provides a meaningful experience of the child with the natural environment. And, through their voices, their expressions, their gestures and laughter, become able to build their knowledge and reframe the experiences in the Botanical Garden. The research shows, however, how vital is to create opportunities for children's participation in the knowledge construction process.